Studies of the Thermovoltaic Effect in Semiconductors in the Medium Temperature Range - Vladimir V. Kaminskiy; Sergey M. Solov'ev; Natalia V. Sharenkova; Mikhail M. Kazanin; Nikolay M. Sudak; Merab I. Zaldastanishvili (Известия высших учебных заведений России: Радиоэлектроника, 2020)
Introduction. A conversion of thermal energy into electrical energy is an urgent task. The thermovoltaic effect (TVE) found in samarium sulfide (SmS ) makes it possible to solve a higher efficiency problem as compared with classical thermoelectric generators operating on the basis of the Seebeck effect. TVE in SmS, is manifested in an appearance of voltage pulses of 0.05 V in continuous mode when a sample is heated to 470 K. Generation of electromotive force (EMF) is associated with a presence of a concentration gradient of defective Sm ions in sulfur sublattice vacancies, with a change in their valence (Sm2+ ® Sm3++e-) and with electronic Mott transitions. TVE discovered subsequently in ZnO, Ge, Si, and in some complex semiconductors, reached only 0.01 V.Aim. To increase the magnitude of the generated voltage and the operating temperature at TVE.Methods and materials. By the method of synthesis from simple substances, raw materials were obtained from which SmS/Sm1-xLnxS sandwich-type heterostructures were created, where Ln = Eu, Yb. In addition, samples based on a classical thermoelectric PbTe with different degrees of doping of the layers obtained by pressing at high temperature in a vacuum were investigated. On the unique equipment, excluding temperature gradients in samples, TVE was studied.Results. It was shown that an increase in the EMF value and in the operating temperature had been achieved due to the penetration of donor levels by doping. In doped samples on the basis of SmS, a generation of EMF up to 0.15 V was observed in continuous mode at T = 700 K. TVE detected in the n-type thermoelectric semiconductor heterostructure PbTe, make it possible to obtain the magnitude of the generated voltage of near 0.06 V in the medium temperature mode.Conclusion. The achieved results exceed the previously known ones and give grounds to continue research with the aim of developing semiconductor converters operating on the basis of TVE.